2012
DOI: 10.1007/s12020-012-9714-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short- and long-duration hypothyroidism on hypothalamic–pituitary–adrenal axis function in rats: In vitro and in situ studies

Abstract: The purpose of this study is to assess the effects of hypothyroidism on the hypothalamic-pituitary-adrenal (HPA) axis; the functional integrity of each component of the HPA axis was examined in short-term and long-term hypothyroidism. Neuropeptide synthesis, release, and content were evaluated in vitro both in the hypothalamus and anterior pituitary, and corticosterone release was assessed in primary adrenal cell cultures at 7 (short-term) and 60 days (long-term hypothyroidism) after thyroidectomy in male rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 33 publications
0
17
0
2
Order By: Relevance
“…Interestingly, in our study it was observed that the postnatal hypothyroidism group had the longest immobility time. Johnson et al (36) found that duration of hypothyroidism had different effects on the HPA axis in rats. According to their study, short-term hypothyroidism was associated with increased pituitary corticotroph responsiveness to corticotropin-releasing hormone in contrast with long-term hypothyroidism (36).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in our study it was observed that the postnatal hypothyroidism group had the longest immobility time. Johnson et al (36) found that duration of hypothyroidism had different effects on the HPA axis in rats. According to their study, short-term hypothyroidism was associated with increased pituitary corticotroph responsiveness to corticotropin-releasing hormone in contrast with long-term hypothyroidism (36).…”
Section: Discussionmentioning
confidence: 99%
“…This situation has been explained by decreased CRH mRNA expression in the hypothalamic paraventricular nucleus. At the adrenal level, in long-standing hypothyroidism, a significant reduction in cortisol secretion after ACTH has been documented in primary adrenal cell culture [15]. This finding was also supported by Tohei et al who suggest that hypothyroidism directly causes adrenal dysfunction and that hypersecretion of CRH and arginine vasopressin is due to a reduction in the negative feedback effect of glucocorticoids [23].…”
Section: Discussionmentioning
confidence: 70%
“…Once patients are clinically stable, glucocorticoids are discontinued. This therapeutic approach is based on small series of cases that have described transient adrenocortical impairment due to thyroid dysfunction and vice versa [815]. Most of the evidence, however, has methodological design problems that make the clinical implications of these conclusions uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Various correlations have been reported between thyroid hormone status and secretion of CRH, ACTH, or glucocorticoid. For example, in humans and animal models, hyperthyroidism may be associated with increased secretion (49 -52) and hypothyroidism with decreased secretion of glucocorticoid (53,54), possibly reflecting changes in adrenal function or sensitivity of the adrenal to ACTH. One explanation for these phenomena is that TR␤1 modifies the sensitivity of the adrenal cortex.…”
Section: A Tr␤1-positive Zone Of the Adrenal Inner Cortexmentioning
confidence: 99%